2018
DOI: 10.1016/j.bj.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

In silico prediction of T- and B-cell epitopes in PmpD: First step towards to the design of a Chlamydia trachomatis vaccine

Abstract: BackgroundChlamydia trachomatis is the most common sexually transmitted bacterial infection globally. Currently, there are no vaccines available despite the efforts made to develop a protective one. Polymorphic membrane protein D (PmpD) is an attractive immunogen candidate as it is conserved among strains and it is target of neutralizing antibodies. However, its high molecular weight and its complex structure make it difficult to handle by recombinant DNA techniques. Our aim is to predict B-cell and T-cell epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Particularly, amino acid substitutions (E484K and N501Y) in conformational epitopes were found in the RBD of the S protein (yellow). Reports suggested that amino acid substitutions of the conformational epitopes lead to viral reinfection and changes of vaccine efficacy ( Russi et al, 2018 ). Thus, our in silico study suggests that the mRNA vaccine efficacy partially changes against the variants ( Russi et al, 2018 ; Sahin et al, 2020 ), although this should also be examined in vitro and in vivo .…”
Section: Sars-cov-2 Genetic Diversitymentioning
confidence: 99%
“…Particularly, amino acid substitutions (E484K and N501Y) in conformational epitopes were found in the RBD of the S protein (yellow). Reports suggested that amino acid substitutions of the conformational epitopes lead to viral reinfection and changes of vaccine efficacy ( Russi et al, 2018 ). Thus, our in silico study suggests that the mRNA vaccine efficacy partially changes against the variants ( Russi et al, 2018 ; Sahin et al, 2020 ), although this should also be examined in vitro and in vivo .…”
Section: Sars-cov-2 Genetic Diversitymentioning
confidence: 99%
“…This interaction is at the core of the adaptive immune system, which among others is responsible for immunological memory and antigen-specific responses in vertebrates [ 2 ]. The ability to identify these binding areas in the antigen’s sequence or structure is important for the development of synthetic vaccines [ 3 , 4 , 5 ], diagnostic tests [ 6 ], and immunotherapeutics [ 7 , 8 ], especially in the COVID-19 era. Focus on these applications through the lens of epitope discovery has gained attention over the years, especially in regard to the safety benefits of synthetic vaccine development [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This interaction is at the core of the adaptive immune system, where among others is responsible for immunological memory and antigenspecific responses in vertebrates. The ability to identify these binding areas in the antigen's sequence or structure is important for the development of synthetic vaccines [1][2][3], diagnostic tests [4] and immunotherapeutics [5,6]. Focus on these applications, through the lens of epitope discovery, has gained attention over the years, especially in regard to the safety benefits of synthetic vaccine development [7].…”
mentioning
confidence: 99%